2002
DOI: 10.1191/0267659102pf556oa
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte filtration in lung transplantation

Abstract: Controlled reperfusion of the transplanted lung has been used in nine consecutive patients to decrease manifestations of lung reperfusion injury. An extracorporeal circuit containing a roller pump, heat exchanger and leukodepleting filter is primed with substrate-enhanced reperfusion solution mixed with approximately 2000 ml of the patient's blood. This solution is slowly recirculated to remove leukocytes prior to reperfusion. When the pulmonary anastomoses are completed, the pulmonary artery is cannulated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The intrapulmonary leukocyte pool and blood leukocytes are considered as a trigger of IR-injury [ 24 , 44 - 46 ]. Although many investigations have confirmed the role of neutrophils in reperfusion injury [ 9 , 24 , 44 , 47 ], other have questioned neutrophil involvement [ 48 ]. One report of Fiser et al could show that in the earliest phase of reperfusion injury the donor (resident) pulmonary leukocyte pool plays an important role [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrapulmonary leukocyte pool and blood leukocytes are considered as a trigger of IR-injury [ 24 , 44 - 46 ]. Although many investigations have confirmed the role of neutrophils in reperfusion injury [ 9 , 24 , 44 , 47 ], other have questioned neutrophil involvement [ 48 ]. One report of Fiser et al could show that in the earliest phase of reperfusion injury the donor (resident) pulmonary leukocyte pool plays an important role [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the documented effectiveness of this approach after myocardial ischaemia [ 20 ] or ischaemia of the lower extremities [ 20 , 21 ] equivalent data about controlled reperfusion of the lungs are rare. In other reports beneficial effects of controlled reperfusion by changing the compounds of the first line perfusate solution [ 22 , 23 ] and leukocyte depletion [ 9 , 22 , 24 ] were described. In rats [ 25 ] and in rabbits [ 26 ] it was reported that PCR improved lung function after ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…34 Many authors confirmed these findings in experimental settings. 35 ¡ 37 Lick et al 38 and Kurusz et al 39 described the importance of this technique when used in humans.…”
Section: Discussionmentioning
confidence: 99%